2008
DOI: 10.1089/mdr.2008.0845
|View full text |Cite
|
Sign up to set email alerts
|

Clusters of Infections in Horses with MRSA ST1, ST254, and ST398 in a Veterinary Hospital

Abstract: During 2006 and 2007 small clusters of methicillin-resistant Staphylococcus aureus (MRSA) infections in horses were recorded in different clinical departments of a veterinary university. The infections were caused by different MRSA clones (ST1, ST254, and ST398). In the same time, nasal colonization of veterinarians, veterinary personnel, and students was observed indicating transmission to humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
110
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(117 citation statements)
references
References 24 publications
4
110
3
Order By: Relevance
“…Clonal complexes CC1 and CC8 were also observed in methicillin-resistant Staph. aureus (MRSA)-positive horses (Cuny et al, 2008;Walther et al, 2009), whereas CC9 was identified in pigs and pig farmers (Armand-Lefevre et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clonal complexes CC1 and CC8 were also observed in methicillin-resistant Staph. aureus (MRSA)-positive horses (Cuny et al, 2008;Walther et al, 2009), whereas CC9 was identified in pigs and pig farmers (Armand-Lefevre et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Alleles, ST, and clonal complexes (CC; groups of closely related ST) were assigned using the MLST database. Bovine-associated CC were distinguished from CC associated with other hosts based on the MLST database and literature (ArmandLefevre et al, 2005;Smith et al, 2005b;Aires-de-Sousa et al, 2007;Rabello et al, 2007;Cuny et al, 2008;Deurenberg and Stobberingh, 2008;Ikawaty et al, 2009;Walther et al, 2009;Hasman et al, 2010;Weese and van Duijkeren, 2010). Clonal complexes were defined to be bovine adapted if isolates belonging to those CC were frequently found in milk samples, and included CC50, CC97, CC151, and CC479.…”
Section: Genotypingmentioning
confidence: 99%
“…17,31,35,38,42 Specific MRSA belonging to clonal complexes CC1, CC5, CC8, CC22, CC59, CC88, CC398, and mainly to spa type t002, t008, t009, t011, t020, t022, t032, t034, t036, t064, t127, t166, t186, t216, t451, t588, t1197, t1451, and t2123 have been identified as a cause of nosocomial infections in numerous equine clinics. 9,27,[37][38][39]43 S. aureus can colonize the skin and mucosa, especially nasal mucosa, of healthy horses and humans, which then acts as a reservoir for MRSA and contributes to its spread into the community and hospitals. 14,35,38,40 Horses entering the hospital have been shown to contribute to the introduction and spread of MRSA in the clinic.…”
mentioning
confidence: 99%
“…Although the CC8-SCCmec IV genotype has been the most frequently found, CC398-SCCmec IV has recently become a major genotype. CC398-SCCmec IV was irst found from infected horses in the Veterinary University of Vienna in Austria [222]. CC398 isolated from nasal samples of horses in the Netherlands and Belgium exhibited high prevalence rates, 9.3 and 10.9%, respectively [227,229].…”
Section: Equine Mrsamentioning
confidence: 94%
“…Multidrugresistant ST8 MRSA was detected in Belgium, Germany, Swizerland, and the USA. A single locus variant of ST8 classiied as ST254 MRSA was isolated from horses in Austria, Germany, Ireland, and the UK [183,208,222,223]. Twelve diferent MLST types have been reported and most of the MRSA strains were grouped into the CC8 or CC398 classes [224].…”
Section: Equine Mrsamentioning
confidence: 99%